Trade and investment in the Americas (OAS WashingtonUS, 2000)
Focuses on the economic situation in the Andean Region as well as on political trends. Highlights foreign trade in Latin America in the 1990s. Looks at the FTAA and the Trade Negotiating Authority
Keywords: TRADE